PENERAPAN AKUNTANSI BERDASARKAN SAK EMKM PADA USAHA MIKRO DODOL JATON DI DESA REKSO NEGORO - Putri, Ayu Anggita; Mattoasi, Mattoasi; Mendo, Andi Yusniar (ITB AAS Indonesia Surakarta, 2024)
This study aims to describe the application accountancy based on SAK-EMKM in UMKM Dodol Jaton in Reksonegoro Village. This study used a qualitative method with a descriptive approach using primary data sources obtained directly from observation and interviews as well as documentation data. The research location is located at Dodol Li Tarni, Reksonegro Village. The results of the research conducted show that K UMKM Dodol Li Tarni Not yet apply recording accountancy based on applicable standards namely SAK EMKM. UMKM Dodol Li Tarni has apply accountancy in activity, however until moment This Still limited to stages collection proof transactions and records proof transaction without terminated with exists report finance Good report in a manner general nor report finance based on SAK EMKM. On research This researcher has do drafting report finance Dodol li Tarni is based on SAK EMKM which consists of from report position finance, profit losses and notes on report finance. With drafting the perpetrator business feel helped Because can know condition finance effort.